(untitled) (Asian-Australasian Journal of Bioscience and Biotechnology, 2020)
The present study was conducted to evaluate the frozen semen quality in terms of different motility patterns and fertility of imported pure Holstein Friesian and Sahiwal breeding bulls maintained under farming condition of Bangladesh. 100% pure Holstein Friesian and Sahiwal breeding bulls were imported and thereafter reared in the American dairy limited (ADL). Semen samples were collected once a week, processed and frozen in the laboratory of ADL. On the day of collection, semen volume and sperm concentration measured immediately after collection. Different motility patterns of spermatozoa (progressive, fast, slow, local, immotile) were measured by Computer Assisted Semen Analyzer (CASA). Effect of breed was found significant (p<0.05) on semen volume and sperm concentration. The semen volume (ml/ejaculate) and sperm concentration (×106) were found to be 6.13±0.28 and 1664.28±62.41 in Holstein Friesian breeding bulls whereas 5.26±0.17 and 2036.00±43.99 in Sahiwal bulls, respectively. The progressive motility, fast motility, slow motility and local motility were significantly (p<0.05) higher in Holstein Friesian bulls than that of Sahiwal bulls both before and after freezing. Different motility patterns such as progressive, fast, slow, local and immotile motility were found to be 89.22±0.45%, 75.97±0.67%, 9.10±0.36%, 4.25±0.15% and 10.05±0.41% in Holstein Friesian bulls whereas 84.98±0.89%, 65.99±0.92%, 11.88±0.37%, 5.65±0.19% and 15.69±0.54% in Sahiwal breeding bulls, respectively before freezing. On the other hand, after freezing, the progressive, fast, slow, local and immotile spermatozoa were found to be 68.19±0.46%, 53.39±2.01%, 9.21±0.46%, 8.47±0.72% and 26.76±2.01% in Holstein Friesian bulls whereas 56.54±0.25%, 42.52±0.67%, 11.11±0.55%, 13.04±1.24% and 30.45±1.58% in Sahiwal bulls, respectively. Non-return rate was found insignificant between the breeds and it was 64.19% in Holstein Friesian and 64.71% in Sahiwal bulls. In conclusion, frozen semen quality of Holstein Friesian pure breed is better than that of Sahiwal breeding bulls but fertility of both breeds are similar. Therefore, frozen semen of both breeds can be used in the field level for the genetic improvement of cattle. Asian Australas. J. Biosci. Biotechnol. 2020, 5 (1), 33-41